Location Preferences for Accessing Long-Acting Injectable Pre-Exposure Prophylaxis (LA-PrEP) Among Men Who Have Sex With Men (MSM) Currently on Daily Oral PrEP - Jennifer L. Glick PhD, MPH; Danielle F. Nestadt PhD, MPH, MSW; Travis Sanchez DVM, MPH; Kevin Li MPH; Marissa Hannah MPH; M Keith Rawlings MD; Alex R. Rinehart PhD; Supriya Sarkar PhD, MPH; Vani Vannappagari PhD, MPH, MBBS (Journal of the International Association of Providers of AIDS Care)
We investigated men who have sex with men's (MSM) location preferences for long-acting injectable pre-exposure prophylaxis (LA-PrEP). MSM ( n  = 1076) who completed the 2021 American Men's Internet Survey, were currently prescribed oral PrEP, and expressed LA-PrEP interest reported location preferences for receiving LA-PrEP: healthcare provider (HCP) setting, pharmacy, or at-home. HCP settings were preferred by 60% of participants; 26% preferred home and 14% preferred pharmacy. In adjusted models, high healthcare stigma was associated with preferring pharmacy and at-home versus HCP, while high friends/family stigma was associated with preferring HCP settings versus pharmacy. Healthcare access history was associated with preference for HCP setting versus home. Being 25 to 29 or 30 to 29 years old versus 40+ was associated with preferring HCP versus home. Private insurance was associated with location preferences. Findings support the need for multiple LA-PrEP service locations to best reach MSM and highlight multiple complex factors that influence such preferences.